Enhancing Computational Thinking in STEM Education through Interactive Programming Media: Evidence of an Equalizing Effect from a Quasi-Experimental Study - Widodo, Suprih; Alifah, Aisyah Husna; Septiadi, Jaka; Sari, Dian Permata; Barri, Muhamad Akda Fathul; Maulida, Rahma (Journal of Educational Science and Technology (EST), 2025)
Computational Thinking (CT) has increasingly been recognized as a foundational competence in STEM education; however, effective pedagogical strategies that support equitable development of CT skills across students with diverse initial abilities remain underexplored. This study examines the impact of interactive programming media on students’ CT development within a STEM learning context. Employing a quasi-experimental design, two groups of upper secondary students participated in either Code.org–supported instruction or conventional learning. Students’ CT skills were assessed before and after the intervention using a CT-oriented problem-solving instrument.The findings indicate that students who engaged with interactive programming activities demonstrated substantially greater improvement in overall CT performance compared to those in conventional learning environments. Moreover, the results suggest that learning gains were largely independent of students’ initial ability levels, indicating an equalizing effect of interactive programming-based instruction. Improvements were observed across core CT components, including decomposition, abstraction, pattern recognition, and algorithmic thinking. These findings contribute to the theoretical discourse on CT pedagogy by highlighting the role of interactive programming environments as mechanisms that mediate learning equity in STEM education. Pedagogically, the study underscores the potential of block-based programming platforms to support inclusive and conceptually grounded CT learning, particularly in contexts characterized by heterogeneous student readiness.